The Mediating Role of Passenger Satisfaction: Examining Servqual and Repurchase Intentions at Tanjung Wangi Port Title - Elmas, Muhammad Syarif Hidayatullah; Sari, Mila Diana (Ilomata International Journal of Management, 2026)
This research examines the associations between terminal service quality (SERVQUAL), passenger satisfaction, and repurchase intention at Tanjung Wangi Port, Banyuwangi, in response to the 6.55% passenger growth recorded in late 2025. While prior maritime studies have predominantly focused on international hub ports, this study addresses an empirical gap by investigating the unique dynamics of domestic passenger terminals, specifically how physical service consistency and staff responsiveness relate to post-purchase behavior. Utilizing an explanatory quantitative design with Structural Equation Modeling (SEM) analysis of 120 respondents, the study identifies that SERVQUAL is significantly associated with both satisfaction (P=0.024) and repurchase intention (P=0.010). The findings highlight that passenger satisfaction serves as a critical mediator, bridging the relationship between tangible terminal facilities and long-term loyalty. By positioning the research within the specific context of domestic maritime transport, these results provide a nuanced understanding of how SERVQUAL dimensions function outside of major global hubs. Ultimately, the study suggests that port management should prioritize the synergy between physical infrastructure and human-led responsiveness to maintain competitiveness against alternative transportation modes.